2004
DOI: 10.1016/j.rmed.2003.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Home mechanical ventilation in Sweden—inequalities within a homogenous health care system

Abstract: We examined local differences in prescription pattern of home mechanical ventilation (HMV) within the homogenous health care system in Sweden. We used 6 years prospective data from the national HMV Register covering the entire Swedish HMV patient population (more than 1000 patients). The treatment prevalence of HMV in Sweden, January 1, 1996 was 6.2/100,000 and January 1, 2002 10.5/100,000 with a steady increase each year in all counties. The differences between leading and non-leading counties showed a tenden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(52 citation statements)
references
References 5 publications
0
50
0
2
Order By: Relevance
“…A substantial increase in the number of patients treated with HMV was noted in the 1990s. [12][13][14] In 2001, the prevalence of HMV was estimated as 6 patients/100,000, 1 and this number further increased to 16 -20 patients/100,000 in 2009. 15 This increase was associated with a distinct shift in underlying diseases from neuromuscular and restrictive lung diseases to obesity hypoventilation syndrome 16 and end-stage COPD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A substantial increase in the number of patients treated with HMV was noted in the 1990s. [12][13][14] In 2001, the prevalence of HMV was estimated as 6 patients/100,000, 1 and this number further increased to 16 -20 patients/100,000 in 2009. 15 This increase was associated with a distinct shift in underlying diseases from neuromuscular and restrictive lung diseases to obesity hypoventilation syndrome 16 and end-stage COPD.…”
Section: Introductionmentioning
confidence: 99%
“…15 This increase was associated with a distinct shift in underlying diseases from neuromuscular and restrictive lung diseases to obesity hypoventilation syndrome 16 and end-stage COPD. 14,17 Almost all data on HMV published to date come from well-developed areas around the world: United States, 5 Western European countries, 1,2,12,14,15 Australia and New Zealand, 16 and Hong Kong. 18 Data about HMV in other countries are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…There was considerable variation in the proportion of patients treated for lung disease or NMD when compared with other countries [19]. Data on HMV usage are scarce around the world, with comparable data available only in Hong Kong, Norway and Sweden [20][21][22]. Previous small studies have examined the situation in Australia [23], and shown that the treatment is well tolerated by local populations [24]; however, no recent or comprehensive data are available for the region as a whole.…”
mentioning
confidence: 99%
“…The Eurovent Survey found that HMV variability concerned both the number of prescriptions and the profile of patients for whom this treatment was prescribed, neither of which was related to the characteristics of the healthcare system or the economic situation in the country involved [1]. The national Swedish HMV register also highlighted variability in prescription within the country itself, despite a similar level of healthcare coverage [14,15]. In Denmark, there are only 2 centers that prepime pime pime pime p pi im me e EDITRICE …”
Section: Discussionmentioning
confidence: 99%